Novel AHR ligand AGT-5 ameliorates type 1 diabetes in mice through regulatory cell activation in the early phase of the disease - Jonić, Natalija; Koprivica, Ivan; Kyrkou, Stavroula G.; Bistas, Vasileios-Panagiotis; Chatzigiannis, Christos; Radulović, Nataša; Pilipović, Ivan; Jovanović, Andjelina; Jovanović, Milan B.; Dimitrijević, Mirjana; Tzakos, Andreas G.; Stojanović, Ivana (Frontiers in Immunology, 2024)
Type 1 diabetes (T1D) is an autoimmune disease with a strong chronic inflammatory component. One possible strategy for the treatment of T1D is to stimulate the regulatory arm of the immune response, i.e. to promote the function of tolerogenic dendritic cells (tolDC) and regulatory T cells (Treg). Since both cell types have been shown to be responsive to the aryl hydrocarbon receptor (AHR) activation, we used a recently characterized member of a new class of fluorescent AHR ligands, AGT-5, to modulate streptozotocin-induced T1D in C57BL/6 mice. Prophylactic oral administration of AGT-5 reduced hyperglycemia and insulitis in these mice. Phenotypic and functional analysis of cells in the pancreatic infiltrates of AGT-5-treated mice (at the early phase of T1D) revealed a predominantly antiinflammatory environment, as evidenced by the upregulation of tolDC and Treg frequency, while CD8 + cell, Th1 and Th17 cells were significantly reduced. Similarly, AGT-5 enhanced the proportion of Treg and tolDC in small intestine lamina propria and suppressed the activation status of antigen-presenting cells through down-regulation of co-stimulatory molecules CD40, CD80 and CD86. The expression levels of Cyp1a1, controlled by the AHR, were increased in CD4 + , CD8 + and Treg, confirming the AHR-mediated effect of AGT-5 in these cells. Finally, AGT-5 stimulated the function of regulatory cells in the pancreatic islets and lamina propria by upregulating indoleamine 2,3-dioxigenase 1 (IDO1) in tolDC. These findings were supported by the abrogation of AGT-5-mediated in vitro effects on DC in the presence of IDO1 inhibitor. AGT-5 also increased the expression of CD39 or CD73 ATPdegrading ectoenzymes by Treg. The increase in Treg is further supported by the upregulated frequency of IL-2-producing type 3 innate lymphoid cells (ILC3) in the lamina propria. Anti-inflammatory effects of AGT-5 were also validated on human tonsil cells, where in vitro exposure to AGT-5 increased the proportion of immunosuppressive dendritic cells and ILC3. These results suggest that AGT-5, by stimulating AHR, may promote a general immunosuppressive environment in the pancreas and small intestine lamina propria at the early phase of disease, and thereby inhibit the severity of T1D in mice.